Malignancy during pregnancy in Japan: an exceptional opportunity for early diagnosis - Masayuki Sekine; Yoshiyuki Kobayashi; Tsutomu Tabata; Tamotsu Sudo; Ryuichiro Nishimura; Koji Matsuo; Brendan H. Grubbs; Takayuki Enomoto; Tomoaki Ikeda (BMC, 2018)
Abstract Background Malignancy during pregnancy has become a significant cause of maternal death in developed countries, likely due to both an older pregnant population, and increases of cervical cancer in younger women. Our aim is to investigate the clinical aspects of malignancy during pregnancy in Japan and to use this information to identify opportunities for earlier detection and treatment. Methods We provided a questionnaire to 1508 secondary or tertiary care hospitals in Japan. We reviewed the clinical characteristics of cases with malignancy during pregnancy for the period of January to December, 2008. From the 760 institutions which responded, we obtained clinical information for 227 unique cases. The questionnaire provided clinical information, including disease site, pregnancy outcome and how the disease was detected. Results The most common type of malignancy was cervical cancer (n = 162, 71.4%) followed by ovarian (n = 16, 7.0%) and breast cancer (n = 15, 6.6%). Leukemia (n = 7, 3.1%), colon cancer (n = 5, 2.2%), gastric cancer (n = 5, 2.2%), malignant lymphoma (n = 4, 1.8%), thyroid cancer (n = 3, 1.3%), brain cancer (n = 3, 1.3%), endometrial cancer (n = 2, 0.9%), and head and neck cancer (n = 2, 0.9%) accounted for the remaining cases. Overall, gynecological malignancies accounted for 79.3% (95% confidence interval 74.0-84.6) of pregnancy associated malignancies diagnosed in the present study. The majority of cervical cancers, 149 (92.0%) of 162, were diagnosed by a Pap (Papanicolaou) smear during early gestation. Ten (62.5%) of the ovarian cancer cases were diagnosed by ultrasonography during a prenatal checkup or at the time of initial pregnancy diagnosis. Out of 14 breast cancers, only one (7.1%) was diagnosed by screening breast exam. Conclusions From this study, we reaffirm the clear and significant benefits of prenatal checkups starting at an early gestational age for the detection of gynecological cancers during pregnancy. Conversely, breast cancer detection during pregnancy was poor, suggesting new strategies for early identification of this disease are required.